Managing powdery mildew (Oidium sp.) of blackberry (Rubus glaucus). A participatory research approach (Bioagro, 2025)
Blackberries are a key source of income for many families, including small and medium-sized producers in Ecuador. There has been a growing need to contribute to research on controlling a disease, powdery mildew, that has been causing significant production losses in recent years. The country has approximately 5,000 hectares of blackberry crops, involving around 15,000 producers in the Ecuadorian highlands. This research was conducted to evaluate the chemical control of powdery mildew (Oidium sp.) in blackberry (Rubus glaucus) using participatory research.  A completely randomized block design was used with 3 treatments, 3 repetitions at each parcel of seven participant farmers. Three fungicide molecules were tested: Accord (difenoconazole), Sulflox (micronized sulfur), and ZT (hydrogen peroxide–27 %). The applications of fungicides were carried out two times and incidence and severity data were taken at 5 and 15 days. For yield, blackberries were counted and weighted. Initial and final surveys to farmers were carried out, accompanied by training.  Analysis of variance and Tukey's test (a = 0.05) were done for incidence, severity, and yield. Participatory research was detailed by means of previous knowledge and the assimilation of chemical treatment for powdery mildew. The best product for control of powdery mildew in all localities was Accord (difenoconazole). San José location had the best control of incidence (15.7 %). Farmers successfully complied with re-entry period in their orchards, in addition to adding Accord to their chemical control of powdery mildew.
Keywords: Disease control; incidence; severity